2020
DOI: 10.1038/s41598-020-69328-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of synovitis in early knee osteoarthritis by MRI and serum biomarkers in Japanese general population

Abstract: To investigate synovitis' influence on early knee osteoarthritis (EKOA) by serum biomarkers and magnetic resonance imaging (MRI) findings in Japanese women. We enrolled 255 women aged 30-70 without radiographic abnormalities (Kellgren-Lawrence grade ≥ 2). Knee injury, OA outcome scores (KOOS), clinical examinations, and standing radiograph were used for classification criteria of EKOA. Participants were classified into normal knee group and EKOA group. All participants underwent MRIs of their right knee. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…In addition to the above-mentioned work of inflammatory biomarkers, the levels of CRP, IL-6, and TNF-α were reported in other studies. Although these biomarkers were found unchanged in early OA individuals [55,63,65], changes were observed in athletes. For marathoners, one study reported unchanged levels of TNF-α [67], others showed increased levels not only of TNF-α but also of CRP and IL-6 [66][67][68]70].…”
Section: Inflammatory Moleculesmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition to the above-mentioned work of inflammatory biomarkers, the levels of CRP, IL-6, and TNF-α were reported in other studies. Although these biomarkers were found unchanged in early OA individuals [55,63,65], changes were observed in athletes. For marathoners, one study reported unchanged levels of TNF-α [67], others showed increased levels not only of TNF-α but also of CRP and IL-6 [66][67][68]70].…”
Section: Inflammatory Moleculesmentioning
confidence: 83%
“…MMP-1 levels did not change in either early OA [72] or marathoners [52], while ADAMTS4 increased in early OA [72]. MMP-3 and -9 levels increased in early OA [65,73] and in marathoners [52,70], and MMP-9 in cyclists [71]. In one study [52], 36 ultramarathoners participated in a race comprising 64 running days without any days of rest.…”
Section: Other Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting result in this study was that serum AMH concentration in the female population having knee OA was associated with serum inflammation markers. Systemic and focal inflammation in the synovium play an important role even in the early phase of knee OA 39 . Inflammation is generally induced by microfragments of cartilages or danger-associated molecular pattern (DAMPS) in synovial fluids and releases several proteases and cytokines, which accelerate the degeneration of articular tissues [40][41][42] .…”
Section: Pre-menopausementioning
confidence: 99%
“…Osteoarthritis (OA), an age-related low-grade inflammatory disease of the synovial joints [1][2][3], is one of the costliest and most disabling forms of arthritis, being highly prevalent and posing a major public health burden [4,5]. Although prevention and an early diagnosis are prerequisites for a favorable outcome, the detailed etiology, pathophysiology, and metabolism of OA remain unclear [6].…”
Section: Introductionmentioning
confidence: 99%